Transanal resection of rectal cancer: a review - Raza, Wasif; Lala, Anil Kumar (International Surgery Journal, 2019)
As an alternative to conventional resection of rectal tumors with low morbidity, the transanal approach has become popular and in-demand. It’s been almost 30 years since the techniques for transanal resection have been evolving steadily. The revolution started with the advent of transanal endoscopic microsurgery in the 80’s. Later, the introduction of transanal minimally invasive surgery improved the access and visibility for surgeons across the world. Concerns have been raised about recurrence rates of cancers with transanal approach and success of subsequent salvage operations. This review is an attempt to concise the available techniques, their results and also to bring about a consensus as to whether it is worth to give our patients an option of transanal resection of rectal cancer.